Designing an intervention to help the quitters quit: A qualitative, intervention co-design study - Judith Dyson; James Skinner; James Crick; Michael G. Crooks (Elsevier, 2023)
Objective: E-cigarettes are increasingly being provided by publicly funded stop smoking services. Our objectives were to understand the challenges and establish the means by which services could best support the use and subsequent discontinuation of e-cigarettes for this purpose. Methods: Semi-structured interviews and co-design workshops with service users and providers of a stop smoking service. Results: Thematic analysis was conducted. Interviews identified: 1. a reluctance to use e-cigarettes for cessation, 2. struggle to quit e-cigarettes (dependency, fear of relapse, compensatory "puffing") and 3. service development needs (consistency of approach). Co-design workshops suggested: 1. facilitation of e-cigarette use through understanding previous failed attempts, 2. offering a longer, two-staged approach to tobacco then e-cigarette cessation, careful timing of behavioural strategies and 3. enhanced communication between providers. Conclusions: Our study suggests additional modifications to smoking cessation support measures when e-cigarettes are used for smoking cessation to address the challenges posed by public health guidance: "smokers should switch to vaping and vapers should stop smoking completely". Innovation: Our study is the first to consider experiences of service users and providers about the challenges of using e-cigarettes for cessation; our co-design group of providers informed nine strategies needed to support this approach in practice.